Clinical significance of CD8‐positive lymphocytes on tumor cell clusters of ascites cell block in ovarian high‐grade serous carcinoma. (8th February 2022) - Iwahashi, Hideki; Miyamoto, Morikazu; Ito, Tsubasa; Suminokura, Jin; Hada, Taira; Ishibashi, Hiroki; Kakimoto, Soichiro; Matsuura, Hiroko; Suzuki, Rie; Minabe, Shinya; Matsukuma, Susumu; Tsuda, Hitoshi; et al.
Abstract: Background: The clinical significance of CD8‐positive (CD8 + ) lymphocytes on tumor cell clusters of ascites cell blocks in patients with ovarian high‐grade serous carcinoma (HGSC) was investigated. Methods: Among HGSC patients who underwent surgery from January 2014 to December 2019, 38 patients with ascites cell block were selected. Using these cell blocks and primary ovarian tumor tissue, the presence of CD8 + lymphocytes and the expression of PD‐L1 were examined immunohistochemically. Tumor cell clusters were defined as cell clumps consisting of more than 10 malignant cells in cell block. Cases with at least one CD8 + lymphocyte in tumor cell cluster were defined as positive CD8 + lymphocytes (Group A); others were defined as negative CD8 + lymphocytes (Group B). The tumor tissue CD8 + lymphocytes were counted mechanically. Clinicopathological features were retrospectively compared between the two groups. Results: In total, 38 cases were identified: 25 (65.8%) in Group A and 13 (34.2%) in Group B. More cases in Group A were positive for CD4 ( p < 0.01), PD‐L1 ( p = 0.02), FoxP3 ( p = 0.02) and had a higher number of CD8 + lymphocytes in the tissue ( p = 0.03). Patients in Group A had better progression‐free survival ( p < 0.01) and overall survival ( p = 0.04). In multivariate analysis, Group A was an independent prognostic factor for both progression‐free survival (hazard ratio, 0.24; p < 0.01) and overall survival (hazard ratio, 0.21; p = 0.03). Conclusion: The presence of CD8 + lymphocytes in tumor cell clusters of ascites was associated with the status of immune reaction in the tissue and prognosis in patients with HGSC and might be useful information of the immune‐associated therapy. Abstract : The presence of CD8‐positive (CD8 + ) lymphocytes on tumor cell clusters of ascites cell blocks in patients with ovarian high‐grade serous carcinoma was associated with the number of CD8‐positive (CD8 + ) lymphocytes and prognosis. This information might be useful for the status of immune reaction.